Gastrointestinal failure score in children with traumatic brain injury - Ying Zhou; Weifeng Lu; Weibing Tang (BMC, 2021)
Abstract Background To review the value of the gastrointestinal failure (GIF) score in children with different degrees of traumatic brain injury (TBI) by analyzing the correlation between outcome and gastrointestinal function. Methods A total of 165 children with TBI who were diagnosed and treated in the surgical intensive care unit (SICU) for longer than 72 h between August 2017 and September 2019 were analyzed. Admission parameters included sex, age, Glasgow Coma Scale (GCS) score, body mass index (BMI), leukocyte count, C-reactive protein (CRP), hemoglobin (Hb), hematocrit (Hct), blood glucose, lactic acid, procalcitonin (PCT), albumin, plasma osmotic pressure, prothrombin time (PT) and activated partial thromboplastin time (APTT). To predict outcomes, the Pediatric Sequential Organ Failure Assessment (SOFA) score, Pediatric Clinical Illness Score (PCIS), and mean GIF score for the first three days were combined. Results The percentage of patients with gastrointestinal dysfunction on the first day was 78.8 %. Food intolerance (FI) and intra-abdominal hypertension (IAH) developed in 36.4 and 21.8 % of the patients, respectively. The GIF score and mean GIF score for the first three days were significantly different between children with different degrees of TBI (P < 0.05); these scores were also significantly different between patients who died and those who survived (P < 0.05). The mean GIF score for the first three days was identified as an independent risk factor for mortality (odds ratio > 1, 95 % confidence interval = 1.457 to 16.016, P < 0.01), as was the PCIS. Receiver operating characteristic (ROC) curve analysis suggested that the mean GIF score for the first three days had the same calibrating power as the PCIS in discriminating the risk of death of children. Conclusions The incidence of gastrointestinal dysfunction in children with TBI is high. The GIF score has the ability to reflect the status of the gastrointestinal system. The mean GIF score for the first three days has high prognostic value for ICU mortality in the SICU.